In Vitro Assessment of Endophytic Bacteria Originating from Cycas rumphii and Dioon spinulosum as Stress-Tolerant Plant Growth-Promoting Bacteria - Al Husni, Muhammad Fariq; Trianti, Irisa; Yusnawan, Eriyanto; Pamungkas, Bayu Aji; Putri, Sastia Prama; Aini, Luqman Qurata (AGRIVITA Journal of Agricultural Science, 2026)
The ability of cycads to grow in harsh environments is thought to be associated with endophytic bacteria in their roots. This study aimed to characterize endophytic bacteria from Cycas rumphii and Dioon spinulosum as stress-tolerant plant growth-promoting bacteria (PGPB). Fine roots of C. rumphii and D. spinulosum were isolated using serial dilution plating and characterized through colony morphological observation, hypersensitivity, antagonistic activity, PGP activity, and abiotic stress tolerance assays. Fourteen isolates were obtained (eight from C. rumphii and six from D. spinulosum), with higher abundance and diversity in D. spinulosum (2.51 × 10¹⁰ CFU/g; H′ = 2.016) than C. rumphii (4.64 × 10⁹ CFU/g; H′ = 1.752). All isolates were non-pathogenic; 92% fixed nitrogen, 92% solubilized phosphate, and one (DS1A) produced IAA (0.200 ppm). Four isolates showed antagonism against Xanthomonas campestris (0.40–0.67 cm inhibition) and tolerance to drought, salinity (5–10%), and moderate heat, with growth at pH 5–6. Molecular identification by 16S rRNA sequencing revealed that CR1A, CR1B, and DS1B belong to Stenotrophomonas maltophilia, whereas DS1A belongs to Bacillus sp. These findings highlight cycads as a source of endophytic PGPB candidates for supporting plant health, particularly when grown in the environmental stress condition areas.